Multimodal neurobehavioral integration in binocular color rivalry: cortical-eye movement analysis under color, location, and combined stimuli - Zhang, Xinni; Lv, Zhineng; Jin, Xuesong; Yun, Lijun; Zhao, Guihong; Chen, Zaiqing (Frontiers in Neuroscience, 2025)
ObjectiveColor and spatial location are key cues influencing visual selection in binocular color rivalry, jointly modulating attentional resource allocation and prefrontal cortex (PFC) activity. However, how these cues—individually and in combination—regulate ocular behavior and PFC activation remains insufficiently understood and lacks systematic empirical investigation.MethodsThis study integrates eye tracking, functional near-infrared spectroscopy (fNIRS), and reaction time measurements to systematically investigate the cortical and oculomotor response characteristics under a binocular rivalry paradigm, focusing on color rivalry (Color stimuli), spatial location (Location stimuli), and their combined (Color & Location stimuli).ResultsThe results revealed that Color stimuli elicited rapid saccades, significant pupil dilation, and a decrease in prefrontal HbO concentration. Location stimuli induced stable saccadic patterns and a typical biphasic HbR response in BA46. The combined Color & Location stimuli triggered significant changes in oculomotor behavior during the later processing stage, accompanied by a marked increase in HbO activation in BA10, suggesting its dominant role in multisensory integration and cognitive resource reallocation. Further coupling analyses showed a significant positive correlation between prefrontal HbO concentration and reaction time (r = 0.555, p < 0.01), and a significant negative correlation between HbO concentration and saccade amplitude (r = –0.376, p < 0.05), consistent with the theoretical predictions of the “neural efficiency–cognitive load trade-off” model. Task-dependent coupling relationship were also observed among oculomotor parameters and between eye movement and cerebral hemodynamic signals.ConclusionColor stimuli induce rapid saccadic behavior and impose higher prefrontal load, Location stimuli engage a more efficient dorsal pathway, while Color & Location stimuli intensify resource rivalry and induce a processing bottleneck, manifested as prolonged reaction times co-occurring with heightened cortical activation.